Hubungan Pengetahuan K3 dan Sikap dengan Unsafe Action pada Mekanik Bengkel di Pulogebang Jakarta Timur - Sri Aji Cakraningrum; Seviana Rinawati; Tyas Lilia Wardani (Journal of Applied Agriculture, Health, and Technology, 2023)
The average motorcycle repair industry grows and operates in the informal sector. Mechanic activities such as oil change services, oil filter replacement, carburetor cleaning, spare parts replacement, and engine disassembly usually come into contact with chemicals such as lubricants or oils, thinners, battery fluids, and gasoline. These activities can lead to work accidents and diseases such as slips, sprains, pinches, falls, and being hit by work equipment such as pliers and screwdrivers. This study aims to analyze the relationship between occupational safety and health knowledge and attitudes towards unsafe actions in mechanics in Pulogebang, East Jakarta. This study uses an analytical observational research method with a quantitative research approach. The research design used was a cross-sectional study conducted at a motorcycle automotive workshop. The sampling method used was a saturated sampling technique with 38 respondents. The tools used in this study were questionnaires on occupational safety and health knowledge, attitude, and unsafe action. The results of the study showed that there was a relationship between occupational safety and health knowledge (p=0.000) and attitude (p=0.000) with unsafe action. Occupational safety and health knowledge had a wald value of 4.732 and attitude had a wald value of 4.806. Therefore, the attitude variable had a greater influence on unsafe action. The Nagelkerke R-Square of 0.582 means that the variables of knowledge and attitude could explain 58.2% of the variance in unsafe action. There is a significant relationship between K3 knowledge and attitude with unsafe action among mechanics in Pulogebang, East Jakarta.